Peran Pendidikan Karakter dalam Pembentukan Perilaku Sosial Siswa - Suprihatin, Elly; Masyitoh, iim siti; rahmat, Rahmat (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
Character education is a fundamental aspect of developing students' personalities and social behavior. This study aims to analyze the role of character education in shaping students' social behavior at SMKS Al-Muawwanah Tasikmalaya. Employing a qualitative approach with a case study method, data were collected through observations, in-depth interviews, and document analysis. The findings reveal that character education at the school is implemented through the integration of character values into classroom learning, social and religious activities, and teacher role modeling. This implementation has positively impacted students' discipline, responsibility, cooperation, and empathy. However, several challenges persist, including limited instructional time, weak evaluation systems, and unsupportive external environments. The study concludes that character education plays a significant role in shaping students' social behavior, although its effectiveness depends on consistent implementation and collaboration among schools, families, and communities. The study recommends strengthening character education strategies systematically and developing a more comprehensive evaluation model.